Pengembangan Media Smart Box Materi Keragaman Budaya Indonesia Pada Siswa Kelas IV Sekolah Dasar - Amelia, Dilla; Djunaidi; Eni Heldayani (Global Action and Education for Society, 2025)
Cultural diversity is a national wealth that needs to be introduced to elementary school students early on so that they can appreciate and preserve cultural heritage. The delivery of cultural material is often less interesting if only delivered through conventional methods, so innovation in media is needed, namely by developing smart box media. This study aims to develop smart box media for Indonesian Cultural Diversity material for grade IV elementary school students that is valid, practical, and effective. The method used is Research and Development (R&D) with the 4D model (Define, Design, Develop, and Disseminate). The subjects of the study were grade IV students of SDN 1 Keman. Data collection techniques used questionnaires and tests, while data analysis techniques included analysis of validity, practicality, and effectiveness. The results showed that the smart box media was declared very valid with a percentage of three validator assessments of 89.96%. The practicality of the media displayed from the student response questionnaire, namely 85.3% stage (one-on-one) and 85.8% stage (small group). The results of the study also showed that the smart box media was effectively used as seen from the increase in learning outcomes before and after using the media, namely the pretest score of 52.38%, while the posttest score increased to 85.71%. Thus, it can be concluded that the smart box media on the material of Indonesian cultural diversity is categorized as valid, practical, and effective.